Analysis of Pedestrian Stress Level Using GSR Sensor in Virtual Immersive Reality - Mudassar, Mahwish; Kalatian, Arash; Farooq, Bilal (Collective Dynamics, 2022)
Level of emotional arousal of one’s body changes in response to external stimuli in an environment. Given the risks involved while crossing streets, particularly at unsignalized mid-block crosswalks, one can expect a change in the stress level of pedestrians. In this study, we investigate the levels and changes in pedestrian stress, under different road crossing scenarios in immersive virtual reality. To measure stress level of pedestrians, we used Galvanic Skin Response (GSR) sensors. To collect the required data for the model, Virtual Immersive Reality Environment (VIRE) tool is used, which enables us to measure participant’s stress levels in a controlled environment. Detailed experiments were conducted over a 5-month period, with 180 participants from four different places in Toronto to cover a heterogeneous population. Data collected are used to develop behavioural models, to observe the contribution of different variables on increasing pedestrian stress level. The initial modelling results suggested that the density of vehicles has a positive effect, meaning as the density of vehicles increases, so does the stress levels for pedestrians. The sociodemographic information has a relationship to individual’s stress levels. It was noted that younger pedestrians have lower amount of stress when crossing as compared to older pedestrians which have higher amounts of stress. Geometric variables has an impact on the stress level of pedestrians. The greater the number of lanes the greater the observed stress, which is due the crossing distance increasing, while the walking speed remaining the same.